ULTRA-WIDEBAND SCANNING ANTENNA ARRAY WIRE EMITTERS - O. A. Yurtsev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The aim of the work is to determine the properties of the ultra-wideband scanning antenna array of wire emitters. A single element of the grid is a three-dimensional antenna Vivaldi. Numerical simulation of antenna arrays and single Vivaldi emitters was carried out by the method of integral equations in the thin-wire approximation using the original program and the MMANA program. The dimensions of all elements of a single emitter are determined by the criterion of matching and the shape of the radiation pattern for operation in the frequency range 2–18 GHz. The described variant of the antenna according to the matching criterion (SWR < 2) has a frequency overlap coefficient of 12. The narrowing of the frequency band of a single emitter in the composition of non-scanning and scanning gratings within the angle of 30 degrees is determined. The article deals with the range properties of antenna arrays depending on the parameters of the emitters and the possibility of phase scanning. It is shown that the greatest frequency band in agreement has a lattice with a minimum step of placement of emitters. In a flat antenna array, when scanning in the H-plane, the frequency band according to the matching criterion decreases by 2–3 times. It is shown that the linear lattice without scanning has a frequency overlap coefficient equal to 6 according to the criterion of matching emitters. This ratio decreases as the phase scan sector increases. In a flat lattice, the frequency overlap coefficient and the phase scan sector are smaller than in a linear lattice and decrease with the number of rows. The reduced antenna array has a number of design advantages and can be used in systems with ultra-wideband signals.